RESTAURANT MENU DESIGN MUARO NEW SAND JAMAK - Weriza, Jusmita; Danyl Malisza; Dahri, Nuraeni; Meri Susanti (Dinasti International Journal of Digital Business Management, 2021)
The design of this application aims to design the menu at the new Android-based Muaro restaurant as an effort to overcome the problem of an ineffective and efficient ordering system. The conventional menu ordering process affects delays and errors in reading orders by the chef. Application design using the android platform. The research method uses the System Development Life Cycle (SDLC) with a Waterfall model approach which consists of 5 stages, namely, a) planning b) analysis c) design d) implementation e) maintenance. The programming language used is PHP, and the database application uses MySql data processing. The system design tool uses the Unified Modeling Language (UML) method using 4 (four) diagrams according to design needs, namely Use Case, Activity Diagram, Class Diagram, Sequence Diagram. This android-based menu design results in a menu ordering process by consumers and knowing the total payment. This application also makes it easier for the chef to know the orders that must be made, as well as produce sales transactions that are fast, accurate, and informative. This menu application can improve menu ordering services by consumers. In general, this application can overcome various problems such as not ordering orders, errors reading orders by the chef.